Empowering Coastal Communities through Sustainable Dried Salted Fish Processing Techniques: Pemberdayaan Masyarakat Pesisir melalui Teknik Pengolahan Ikan Asin Kering yang Berkelanjutan - Ari, Rustan; Manan, La Ode Abdul; Aksara, Fid Aksara; Hastian, Hastian (Universitas Lancang Kuning, 2025)
The empowerment program implemented in Tapuhahi Village, Bombana Regency aims to equip the partner group with knowledge and skills in handling and processing fish into high-quality dried salted fish according to Indonesian national standards. This empowerment utilizes the ABCD method to transfer information and skills to the partner groups to ensure the quality and safety of the dried salted fish produced. The empowerment program showed that 40% of participants had the knowledge and skills to produce quality fish. The results of the post-training evaluation showed that the training successfully imparted essential skills while identifying specific areas for improvement. These insights provide a basis for refining the training to better meet the needs of processors and improve future training outcomes, ensuring the program remains effective and relevant. The implications of the program are reduced post-harvest losses, increased group income, improved product quality and safety, and replication to other processing groups.